2020
DOI: 10.1038/s41419-020-2395-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of topoisomerase IIA (Top2α) induces telomeric DNA damage and T cell dysfunction during chronic viral infection

Abstract: T cells play a critical role in controlling viral infection; however, the mechanisms regulating their responses remain incompletely understood. Here, we investigated the role of topoisomerase IIA (Top2α, an enzyme that is essential in resolving entangled DNA strands during replication) in telomeric DNA damage and T cell dysfunction during viral infection. We demonstrated that T cells derived from patients with chronic viral (HBV, HCV, and HIV) infection had lower Top2α protein levels and enzymatic activity, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 52 publications
1
35
0
1
Order By: Relevance
“…Given the known role of telomeric DNA damage in T cell dysfunction during chronic viral infections 14 , 15 , 21 , 36 38 , and that only PGC-1α, but not PGC1β, was inhibited by KML001 treatment (Fig. 2C, D ), we examined the frequencies of PGC-1α + cells in CD4 T cell subsets in PLHIV, in which we have recently shown an aging phenotype with shortened telomeres 36 and compromised mitochondria (unpublished observations).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the known role of telomeric DNA damage in T cell dysfunction during chronic viral infections 14 , 15 , 21 , 36 38 , and that only PGC-1α, but not PGC1β, was inhibited by KML001 treatment (Fig. 2C, D ), we examined the frequencies of PGC-1α + cells in CD4 T cell subsets in PLHIV, in which we have recently shown an aging phenotype with shortened telomeres 36 and compromised mitochondria (unpublished observations).…”
Section: Resultsmentioning
confidence: 99%
“…Given the known role of telomeric DNA damage in T cell dysfunction during chronic viral infections 14,15,21,[36][37][38] , Fig. 1 Telomere damage by KML001 impairs mitochondrial functions in human CD4 T cells.…”
Section: Telomere Injury By Kml001 Represses the Pgc-1α Network Govermentioning
confidence: 99%
“…Notably, GAS5 effects on T cell exhaustion during HIV infection may be mediated by mechanism(s) beyond GAS5-miR21 mediated signaling. Bottom: Deficiencies in Top1/2a, ATM, hTERT, and TRF2 that can cause telomeric DNA damage (30)(31)(32)(33)(34)36) are known to contribute to dysfunctional CD4 T cells in HIV patients.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that PLHIV exhibit CD4 T cell exhaustion, senescence, apoptosis, and dysfunction, despite ostensibly complete control of viral replication by ART (30)(31)(32)(33)(34)(35)(36). How T cell functions are dysregulated in ART-controlled PLHIV is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear DNA repair pathways, such as base excision repair and double-strand break repair, can repair damaged mtDNA through nuclear-encoded genes; however, these processes may be deregulated during HIV-infection. For instance, emerging work from our group and others have shown dysregulation of critical DNA damage response proteins, such as ATM, ATR, DNA-PKcs, TOP I/IIα, and p53 in the setting of HIV-infection [ 39 , 43 , 44 , 45 , 46 , 47 , 48 ]. The literature shows that mitochondrial function and signaling pathways become disrupted in the presence of HIV-infection and ART treatment.…”
Section: Introductionmentioning
confidence: 99%